A simplified version of adaptive super‐twisting control. (8th August 2019) - Gutierrez, Susana V.; De León‐Morales, Jesús; Plestan, Franck; Salas‐Peña, Oscar
Summary: In this paper, a simplified super‐twisting control with adaptive gain is proposed for a class of nonlinear uncertain systems. A strong Lyapunov function is constructed to design a sliding mode controller with adaptive gain. Furthermore, the analysis of the finite time convergence towards the equilibrium point of the closed‐loop system is detailed. Regarding previous works from literature, the main contribution of this approach is the simplification of the gain tuning process by maintaining a high level of performance. Finally, simulation results for tracking control of a quadrotor are given to show the performance of the proposed algorithm.